Use Of Guava As A Prevention Of Acute Diarrhea In Toddlers - Zulfiana, Yesvi; Nurul Fatmawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
The 2018 Balitbangkes Basic Health Research (Riskesdas) data shows the prevalence of diarrhea in toddlers is 12.3%. Riskesdas also stated that the most common cause of infant death was diarrhea (31.4%). According to the 2010 diarrhea morbidity survey, the largest proportion of sufferers was in the 6-11 month age group, which was 21.65% (Ministry of Health, 2011). This study aims to get an overview of the use of guava leaves as an effort to prevent acute diarrhea in toddlers.The method used in this study is quantitative, which is to find out an accurate description of the use of guava as an effort to prevent acute diarrhea in toddlers.From the results of the study it was found that most children who experienced diarrhea consumed guava as an alternative treatment by 60%.Giving decoction of guava leaves effective in reducing the frequency of diarrhea when consumed regularly, besides that it can used by the community as traditional medicine that has easy profit, easy way its use, and many residents who plant.It is suggested to mothers of toddlers to use an alternative to giving guava leaves as a treatment or prevention of acute diarrhea in toddlers.